A two-scale hydro-mechanical-damage model for simulation of preferential gas flow in saturated clayey host rocks for nuclear repository. (October 2021) - Yang, Jianxiong; Fall, Mamadou
Abstract: Significant amounts of gases could be generated in the post-phase of radioactive waste repositories, which may deteriorate the integrity of natural host rocks. A safety issue related to the geological disposal facilities concerns the gas migration through saturated host rocks, of which the dominant process is mainly referred to the advective gas flow, accompanied by the formation of micro-fracturing that occurs at the applied gas pressure significantly lower than the minimum principal stress (compressive stress is regarded to be positive here). These fracture formed gas pathways are found to be highly localized and dynamically unstable, which may vary temporally and spatially within the clayey rocks. A multiscale model incorporating the evolving microcracks may be appropriate to address this specific rupture pattern. The model is developed from the periodically distributed microstructures with microcracks in a porous medium. The upscaling method based on the asymptotic expansions leads to the macroscopic hydro-mechanical (HM) governing equations coupled with the normalized microcrack length. Based on the micro-mechanical energy analysis, the time-dependent damage evolution law is constructed that accounts for the subcritical microcrack propagation. The local macroscopic response of the model is analyzed with emphasis on the influence of the microstructural size, the loading rate and the reference crack velocity, which are important factors influencing the localized pathways for gas migration. Two numerical examples of air injection tests on clayey rocks are presented where the highly localized gas pathways are explicitly simulated. The comparison between the model predictions and the experimental results provides in-depth understanding of gas induced fracturing process.